EFFECTS OF THE COVID-19 PANDEMIC ON MALE SEXUAL FUNCTIONING AND ACTIVITY (Vietnam Journal of Community Medicine, 2022)
Background: The acute respiratory infection caused by the SARS-CoV-2 virus has becomea global pandemic. Faced with the nature and complexity of the epidemic, many governmentshave enacted social distancing and isolation measures. These measures cause significantchanges in an individual’s functioning, including sexual functioning and functioning.Aim: Evaluation of the impact of the Covid-19 epidemic on male sexual activity and malesexual function.Methods: Two hundred and seventy men completed a set of telephone interviewquestionnaires. Evaluation of sexual activity and function through collecting and analyzingvariables on the frequency of sexual activity, level of Satisfied sex life, IIEF-5 scale, PEDT,IELT time, orgasm level.Results: Sexual activity: The frequency of sexual intercourse, the frequency of masturbationbefore - during the epidemic was 2.7 ± 0.14 and 2.35 ± 0.18 times/week, respectively(p
Keywords: Covid-19 epidemic, SARS-CoV-2, sexual activity, male sexual function.